Evaluation of performance characteristics of stone mastic asphalt incorporating industrial waste - Oluwasola, E. A. (American Society of Civil Engineers (ASCE), 2016)
Among the numerous advantages of stone mastic asphalt (SMA) is its ability to provide durable surfacing, as well as its high resistance to rutting due to heavy axle loads. The level of research on the utilization of waste and by-products in the construction of SMA is still low, especially in developing countries. To address this gap, this study evaluated the performance characteristics of SMA incorporating electric arc furnace (EAF) steel slag and copper mine tailings (CMT). Mix 1 consisted of 100% granite; Mix 2 was 80% granite, 20% CMT; Mix 3 consisted of 80% EAF steel slag and 20% CMT; and Mix 4 was 40% EAF steel slag, 40% granite, and 20% CMT. The moisture susceptibility of the mixes was within the allowable limits and the mixture prepared with PG 76-22 is more susceptible to water damage. The resilient modulus of ethylene-vinyl acetate (EVA)-modified 80/100 mixes is also greater than PG 76-22 mixtures at both temperatures of 25°C and 40°C for the unaged and aged samples. The obtained results show that the mix containing EAF steel slag and CMT exhibited superior performance to the control mix sample. In conclusion, incorporating EAF steel slag and CMT into the SMA mixture has significantly improved the SMA performance characteristics and simultaneously increased the rutting susceptibility of the mixture.